mGem: Sepsis and antimicrobial resistance in the context of advanced HIV disease - Rachel M. Wake; Nelesh P. Govender (mBio)
ABSTRACT Sepsis triggered by bloodstream infections (BSI) is a significant driver of HIV-related mortality, particularly among in-patients with advanced HIV disease (AHD). Currently, the incidence, etiology, and outcomes of BSI in this population are poorly defined. We review the existing evidence, which shows an increased risk of BSI, particularly with antimicrobial-resistant (AMR) organisms, and higher BSI-associated mortality in patients with AHD. Causative bacterial and fungal pathogens are often unknown, but when identified, limited data show etiology has shifted probably owing to increasing coverage of antiretroviral treatment, antimicrobial prophylaxis, and rising global AMR trends. Further research is crucial to design and refine interventions before, during, and after hospital admission to reduce sepsis-related mortality in patients with AHD.